Frequency and Criteria for Using Corrective Feedback: A Case Study on University Students and Lecturers Perceptions [Criterios y Frecuencia de Uso de Estrategias de Retroalimentación Correctiva: Un Estudio de Caso Sobre Las Percepciones de Estudiantes y Profesores Universitarios] - Orrego-Ramirez, R; Ubeda-Menichetti, R; Singer-Contreras, N (Universidad de Concepcion, 2019)
This study explores students and teachers perceptions towards corrective feedback knowledge, criteria and frequency of use performed by teachers to address grammar errors in English language course units. This research is based on the result analysis of previous studies that have examined types of corrective feedback received by second language (SL) learners (Lyster y Ranta,1997; Sheen, 2004), the extent of noticing it and its uptake Mackey, et al. (2003); Philp (2003), and the conceptualisation of the corrective feedback as a systematic answer to wrong utterances, either implicitly or explicitly (Ellis, R., Loewen, S. y Erlam, R., 2006; Pawlak, 2014). Two data collection methods were used to carry out this research, i.e. a survey and a semi structured interview delivered in focus groups. The first was applied to four levels of learners of an English language teaching programme and the teachers teaching English language of the same programme. Then a semi structured interview was conducted to delve into those representations. Preliminary results show students recognise there is certain coherence between the types of correctives used and their appropriateness. However, data reflect that fifth-year learners and some teachers hold their own representations towards corrective feedback which are inconsistent with the available literature. It is concluded that these findings support the claim that teacher development programmes on SL corrective feedback strategies and methodologies are necessary. © 2019 Universidad de Concepcion. All rights reserved.